Bawean Geotrack: Linkage Between Geodiversity, Biodiversity, And Cultural Diversity for Driving The Acceleration Bawean Island-Gresik Geopark - Harun Arrasyid; Mohammad Adib Maulana; Dhofaeri Wildan; Karimah Karimah (Badan Pelaksana Rinjani-geopark Rinjani Lombok, 2023)
Bawean Island, Gresik Regency is geographically located in the Java Sea, precisely located between Borneo and Java. Currently, Bawean Island is being fought to become a Geological Heritage and continues to be developed, so that it can be proposed as a National Geopark. The Geology, Biology, and Cultural Diversity that exists on Bawean Island are still separate pieces that need further research so that it can be presented in a holistic order as geotourism. The purpose of this study is to examine geosite recommendations on Bawean Island and to reconstruct the geological history of the biological and cultural diversity of the community that developed from the past to the present in a Geosite Distribution Path Map (Geotrack). The methods used are literature review, observation of DEM imagery to determine morphology, and Geosite Potential Survey which is followed by feasibility study calculations based on parameters from the Geological Survey Center. The results of this study are in the form of a Geotrack Map consisting of 24 Geosites (15 Geodiversity, 3 Biodiversity, and 6 Cultural Diversity) which are contained in a digital system in the form of WebGIS so that all elements of society can access it. The occurrence of transgression and marine regression in the past caused by the formation of ancient volcanoes supports the formation of a typical flora and fauna ecosystem on Bawean Island. In addition, the formation of an island in the middle of the Java Sea surrounded by other cultures and civilizations led to the acculturation and cultural assimilation of the Bawean island.